1931
DOI: 10.1073/pnas.17.8.499
|View full text |Cite
|
Sign up to set email alerts
|

Matthiola Incana

Abstract: For more than a month subsequent to the birth of her dilute young, the mutant was so feeble that all hope was given up for her recovery. After this, however, she rallied sufficiently to produce a second litter of three. These all developed intense pigmentation, proving the mutation to have been germinal and to have involved probably one only of the two gametes from which she was derived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1935
1935
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…The lowest and highest numbers of bivalent and quadrivalent chromosomes were both observed in the 'Nobel' cultivar. This finding is consistent with the results obtained by previous work with aneuploid stock flower plants (Frost, 1931).…”
Section: Discussionsupporting
confidence: 94%
“…The lowest and highest numbers of bivalent and quadrivalent chromosomes were both observed in the 'Nobel' cultivar. This finding is consistent with the results obtained by previous work with aneuploid stock flower plants (Frost, 1931).…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, frequency of trisomic plants further reduced when they were used as pollen parent. Higher rate of trisomy transmission through seed (female) parent than pollen (male) parent was also reported in Datura stramonium (Blakeslee and Furnham 1923), Matthiola incana (Frost 1931), tomato (Rick et al 1964), barley (Tsuchiya 1967, Das andBhowmik 1971), jute (Iyer 1968), sorghum (Liang 1979), rye grass (Meijer and Ahloowalia 1981), pearl millet (Minocha et al 1976, Plantago lagopus (Sharma et al 1985), certain trisomics of rice (Khush et al 1984, Hee-Jong et al 1993, Arabidopsis thaliana (vide Meyerowitz and Somerville 1994), Soybean (Xu et al 2000) and in cabbage (Zhang et al 2007) although opposite trend was noticed in tomato (Lesley 1932), maize (McClintock 1929), tobacco (Goodspeed andAvery 1939, 1941), spinach (Tabushi 1958) and Lotus pedunculatus (Chen and Grant 1968). Low rate of transmission of extra chromosome through pollen parent has been due to slower growth of nϩ1 pollen tube than those of n grain (Buchholz and Blakeslee 1922), poor ability of nϩ1 pollen grains to germinate, delayed maturity and pollen sterility (Ramage 1965).…”
Section: Discussionmentioning
confidence: 51%
“…Frost and Mann (1924) had reported that the morphological marker of long and wide leaves was a marker of a cultivar with a high double stock production rate. Previous investigations on the stock flower had shown changes of morphological characteristics in stock plants that give an especially high proportion of double-flowered progenies (Frost andLesley 1927, Emsweller et al 1937). According to Frost and Lesley's study (1927) Fig.…”
Section: -Reproductive Traitsmentioning
confidence: 99%
“…Based on these studies, the basic chromosomal number (n = 7, 2n = 2x = 14) was reported for this plant (Allen 1924, Frost andLesley 1927). Frost (1931) identified aneuploidy in a plant called "Snowflake" with 86% double-flowered progenies: cytological investigation determined additional chromosomes in this type. Philp and Huskins (1931) reported that this additional chromosome had a V shape that was eliminated during meiotic division but remained in mitosis.…”
Section: Introductionmentioning
confidence: 99%